2020
DOI: 10.1016/j.eclinm.2020.100448
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics, risk factors and outcomes among the first consecutive 1096 patients diagnosed with COVID-19 in Kuwait

Abstract: Background: In Kuwait, prior to the first case of COVID-19 being reported in the country, mass screening of incoming travelers from countries with known outbreaks was performed and resulted in the first identified cases in the country. All COVID-19 cases at the time and subsequently after, were transferred to a single center, Jaber Al-Ahmad Al-Sabah Hospital, where the patients received standardized investigations and treatments. The objective of this study was to characterize the demographics, clinical manife… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
153
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 145 publications
(181 citation statements)
references
References 30 publications
(33 reference statements)
19
153
4
Order By: Relevance
“…Compared to European and American countries, the case fatality rate was low in Asian countries. The mortality rate among COVID-19 patients in Bangladesh was 10% [69] followed by Iran and Kuwait 8.06% and 1.73% respectively [73,74]. Among the Asian region, the highest mortality was found in China and South Korea [47,66].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to European and American countries, the case fatality rate was low in Asian countries. The mortality rate among COVID-19 patients in Bangladesh was 10% [69] followed by Iran and Kuwait 8.06% and 1.73% respectively [73,74]. Among the Asian region, the highest mortality was found in China and South Korea [47,66].…”
Section: Discussionmentioning
confidence: 99%
“…The history of smoking among COVID-19 patients increased the risk of mortality. From a study, it was found that smokers had a 767% higher risk of mortality as non-smoker [32,33,74].…”
Section: Discussionmentioning
confidence: 99%
“…For example, the incidence rate ratios between male and female were 1 Table 2. Besides, studies pointed out that most patients had more than one symptom [68,70,71]. Additionally, there were 20.9% of patients without viral pneumonia symptoms [16], which was opposite to previous studies [69,70].…”
Section: Mortality and Fatalitymentioning
confidence: 59%
“…Additionally, there were 20.9% of patients without viral pneumonia symptoms [16], which was opposite to previous studies [69,70]. The asymptomatic cases varied from 21.9%-49.5% [66,68,93,94]. The top 3 common symptoms among mild and severe patients are summarized and displayed in a figure (Figure 3) [12,16,61,70,[95][96][97][98].…”
Section: Mortality and Fatalitymentioning
confidence: 67%
“…Data comprised 3 995 admitted patients between the 24th of February and the 27th of May 2020, and was an extension of a population described earlier elsewhere [17]. All patients, included in the study, tested positive for the SARS-CoV-2 virus using real-time polymerase chain reaction (RT-PCR).…”
Section: Setting and Data Sourcementioning
confidence: 99%